Empirical research on CBBE scale for medical tourism. Issue 3 (27th July 2018) - Guha Roy, Diya; Mukherjee, Srabanti; Bhattacharya, Sujoy
Abstract : Purpose: The medical tourism market across the globe lacks a consolidated, standard customer-based brand equity (CBBE) scale till the present day. The purpose of this research is to theorize a scale with probable existing dimensions and based on prior literature adding culture and infrastructure/superstructure as new components for global comparison among BRICS and SAARC nations. This empirical research initiates laying the foundation of deriving a unified scale. Design/methodology/approach: Extensive literature reviews from leading academic journals, books and web information were used to theoretically propose the scale. R (an open source coding language) was used for quantitative analysis. Findings: Culture (environment index) and infrastructure/superstructure (industry/economic index) were found to be relevant in the context of CBBE scale for medical tourism. The other dimensions are brand awareness, brand association, perceived quality and loyalty. Research limitations/implications: The research literature was fragmented because of international scopes of medical tourism destinations as well as a variety of medical services offered. The dynamic nature of this industry, which is dependent on several factors such as healthcare, cost, related services, tourism etc. made it difficult to access the real contribution of individual items. Practical implications: This paper proposes the foundation to develop a CBBE scale for medical tourism in India, adding culture and infrastructure/superstructure as new dimensions. It opens doors for new research with scale refining, branding assessment and fine-tuning items for the new dimensions. Originality/value: This research is the first of its kind to create a standard CBBE scale for developing countries. It has added a new set of literature and consolidated prior contextual works on culture and infrastructure in reference to medical tourism. The questionnaire is of practical value to hospitals. The interview transcript is novel in nature for future works.